Designing Ambient Assisted Living Applications: An Overview of State-of-the-Art Implementation Concepts - Röcker, Carsten (Modeling, Simulation and Control)
Research in the field of Ambient Assisted Living gained considerable momentum over the last decade and the diversity of existing applications is matched by a broad variety of implementation approaches. This paper takes a closer look at existing work in this field and provides a structured overview over state-of-the-art implementation concepts.
Keywords: Smart medical services; ambient assisted living; E-healt; intelligent environments; ubiquitous and pervasive computing